Molecular basis of toxicity of N-type calcium channel inhibitor MVIIA. (February 2016) - Wang, Fei; Yan, Zhenzhen; Liu, Zhuguo; Wang, Sheng; Wu, Qiaoling; Yu, Shuo; Ding, Jiuping; Dai, Qiuyun
Abstract: MVIIA (ziconotide) is a specific inhibitor of N-type calcium channel, Cav2.2. It is derived from Cone snail and currently used for the treatment of severe chronic pains in patients unresponsive to opioid therapy. However, MVIIA produces severe side-effects, including dizziness, nystagmus, somnolence, abnormal gait, and ataxia, that limit its wider application. We previously identified a novel inhibitor of Cav2.2, ω-conopeptide SO-3, which possesses similar structure and analgesic activity to MVIIA's. To investigate the key residues for MVIIA toxicity, MVIIA/SO-3 hybrids and MVIIA variants carrying mutations in its loop 2 were synthesized. The substitution of MVIIA's loop 1 with the loop 1 of SO-3 resulted in significantly reduced Cav2.2 binding activity in vitro ; the replacement of MVIIA loop 2 by the loop 2 of SO-3 not only enhanced the peptide/Cav2.2 binding but also decreased its toxicity on goldfish, attenuated mouse tremor symptom, spontaneous locomotor activity, and coordinated locomotion function. Further mutation analysis and molecular calculation revealed that the toxicity of MVIIA mainly arose from Met 12 in the loop 2, and this residue inserts into a hydrophobic hole (Ile 300, Phe 302 and Leu 305 ) located between repeats II and III of Cav2.2. The combinative mutations of the loop 2 of MVIIA or other ω-conopeptides may be used for future development of more effective Cav2.2 inhibitors with lower side effects. Highlights: MVIIA/SO-3 hybrids and MVIIA variants carrying mutations in its loop 2 were synthesized. The replacement of MVIIA loop 2 by the loop 2 of SO-3 enhanced the peptide/Cav2.2 binding and decreased its toxicity. Met 12 in the loop 2 contributed to the toxicity of MVIIA. More effective Cav2.2 inhibitors with lower side effects were obtained by the combinative mutations of the loop 2 of MVIIA.